DOZ047.81: Neurodevelopmental outcome in infants with AE: developmental trajectories in the first year of life. (24th June 2019) - Bevilacqua, F; Ragni, B; Valfrè, L; Conforti, A; Braguglia, A; Bagolan, P; Aite, L
Abstract: Background: Esophageal atresia (EA) prognosis have improved significantly over the past three decades. Research and clinical attention has shifted to neurodevelopmental outcomes and quality of life. Aim: The aim of this study wasto examine neurodevelopmental outcomes and to identify clinical and sociodemographic risk factors in a cohort of infants with EA. Methods: An observational prospective longitudinal study was conducted between 2009 and 2017. Neurodevelopment was assessed at 6 and 12 months by Bayley Scales of Infants and Toddler Development—3 rd Edition. Clinical and sociodemographic variables included were gender, birthweight, gestational age, associated malformations, number of hospitalizations, surgeries and dilatations at 12 months, days of mechanical ventilation, parental age, education level, and socioeconomic status. Results: Ninety-six infants were enrolled in the study at 6 months and 73 of them were evaluated also at 12 months. Analysis showed significant differences between motor development at 6 and 12 months (M6 = 95.39, SD = 15.71; M12 = 91.83, SD = 12.87; t  = 0.245, P  = 0.017); significant differences emerged also between cognitive development at 6 and 12 months (M6 = 91.80, SD = 11.70; M12 = 100.92, SD = 15.39; t  = −5.10, p  = .000). Infants with long-gap AE achieved the worst scores in cognitive ( r  = -.28, P  < .01) and motor scales ( r  = -.36, P  < .01) at 6 months and in motor scale at 12 months ( r  = −0.30, P  < 0.05). More days of mechanical ventilation were related to a lower score in both the cognitive (6 months r  = −0.26, P  < 0.05; 12 months r  = −0.26, P  < 0.05) and motor scale (6 months: r  = −0.38, P  < 0.01; 12 months r  = −0.42, P  < 0.01). A major number of interventions in the first year of life were related to lower scores in the motor scale at 12 months ( r  = −0.43, P  < 0.01). Conclusions: Infants operated on for AE are at risk of neurodevelopmental impairment in the first year of life. Findings support the association between neurodevelopmental outcomes and clinical risk factors. Careful interdisciplinary follow-up is essential for early detection of neurodevelopmental delay.